Countering the Western canon: another way of knowing about journalism and media - Mohd Noor Merican, Ahmad Murad (Penerbit UPSI, 2023)
The essays in this book represent my engagement with the epistemological, historical, cultural and societal perspectives of journalism and media. It interprets what is and advocates what would and could be. As the practice with most writing from the university environment, many originated from academic, scholarly and social commitments in one’s vacation. This book introduces another way of knowing journalism and the media. It serves as a rejoinder to the orientation and thinking on journalis, communications and media in Malaysia conditioned by the establishment of journalism/mass communications schools some five decades ago. Apart from exploring non-Western perspectives on media historiography and communication, this book argues for a corpus from a none Euro-American tradition. It calls for reassessing journalism as a sociological and civilizational construct implemented through the curriculum in journalism and media education.